Adsorbate—Adsorbate Association in a One-Component Mobile Adsorption Phase on Energetically Homogeneous Adsorbents - J.K. Garbacz; A. Kopkowski (Adsorption Science & Technology, 1997)
A new description of adsorbate-adsorbate association on energetically homogeneous adsorbents has been presented. Suitable relations have been formulated for the mobile adsorption of a single gas. Experimental adsorption data have been described theoretically by the equations derived. The calculation results demonstrate the good applicability of the proposed idea.